If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 120 + 45n = 0 Solving 120 + 45n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -120 + 45n = 0 + -120 Combine like terms: 120 + -120 = 0 0 + 45n = 0 + -120 45n = 0 + -120 Combine like terms: 0 + -120 = -120 45n = -120 Divide each side by '45'. n = -2.666666667 Simplifying n = -2.666666667
| 2(x-1)=4x-5(x+3) | | -4/9z=24 | | y=x+z-36 | | 5x^2+8-58=0 | | 2368=3.1416*R^2*76 | | (h)(h+7)(2h)=180 | | 15(3n+8)=c | | -2x+1=71+5x | | y+22+3y-14=0 | | f(x)=-x^3-5x^2-2x+1 | | 2368=301416*R^2*76 | | 12r-8s+3r+5s= | | 7x-8=-78 | | 2/9p=-16 | | x^2+16=8 | | logx=10.665 | | 2368=3.1416*R^2 | | -10r+5+-10r= | | 5X+25=2X+127 | | 3+2x+6x=-93 | | 4+6x+7-(-2x)=5 | | 2x+24y=72 | | -10+5+-10r= | | 2x+24=72 | | 11x-y=6 | | D=1/2jw | | 7x-6=60 | | 5x-5+3x+8=19.5 | | -x^2+3=-46 | | -w-(-4)=6 | | 14x-265=5x-13 | | 2*13+26=l |